"This is probably the reason why she resorted to that kind of action": A qualitative analysis of juvenile justice workers attributions for girls' offending. Issue 2 (3rd April 2019) - Burson, Esther; Godfrey, Erin B.; Singh, Sukhmani
Abstract: A large body of evidence suggests that within the juvenile justice system, girls fare worse than boys on several measures, including number of arrests, length of stay, and mental health outcomes while in the system. Scholarship suggests a myriad of gendered social factors that precipitate girls' involvement in the juvenile justice system; however, less is known about how stakeholders within the juvenile justice system perceive the girls they work with or interpret their experiences. The current paper examines the attributions that juvenile justice system workers make about the reasons girls offend. In line with previous research, we identify both internal (personality, character traits) and external (situational) explanations for girls' involvement in the juvenile justice system that correspond to gender stereotypes and expectations of girls. Furthermore, we identify structural attributions as a special subset of external attributions that take into account how larger social, economic, and historical factors shape girls' situations and experiences and contribute to their criminal behavior. These structural attributions have implications for practitioners' views of justice and the role of the juvenile justice system in the lives of girls. We conclude with a set of implications for practice and policy.